2008
DOI: 10.1016/j.cveq.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes

Abstract: In this article, the normal kinetics, morphology and other unique characteristics of equine erythrocytes are reviewed, the influence of the spleen on erythrocyte values is discussed, and selected normal reference intervals are presented. In addition, the classification and causes of anemia and polycythemia are reviewed and the appropriate laboratory tests for accurate diagnosis are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 8 publications
5
26
0
2
Order By: Relevance
“…In Northeastern donkeys, LEU did not present differences (10 ×10 9 /L) (p > 0.05) among the groups, and also remained within the values described in the literature for this species in different breeds around the world (Jordana et al 1998, Lording 2008, Giraldo et al 2013, Garba et al 2015. In these latter publications, LEU ranges from 7×10 9 /L to 11.72×10 9 /L in healthy animals (Boudreaux andEbbe 1998, Garba et al 2015).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In Northeastern donkeys, LEU did not present differences (10 ×10 9 /L) (p > 0.05) among the groups, and also remained within the values described in the literature for this species in different breeds around the world (Jordana et al 1998, Lording 2008, Giraldo et al 2013, Garba et al 2015. In these latter publications, LEU ranges from 7×10 9 /L to 11.72×10 9 /L in healthy animals (Boudreaux andEbbe 1998, Garba et al 2015).…”
Section: Discussionsupporting
confidence: 50%
“…However, due to the way RDW-SD is measured, it has become a more reliable parameter to determine erythrocyte response (Gameleira et al 2011, Garba et al 2015. It has also recently been shown that the combination of MCV and MCHC with RDWs may produce a better understanding and classification of anemia in horses (Lording 2008) and it can be applied to donkeys. In the current animals, MCV resembles those described for Italian donkeys (adults: 54fL; youngsters (1-3 years): 49fL) (Caldin et al 2005), and it is also within the values described for other donkey breeds (Mori et al 2004, Tesfaye et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The erythron is assessed from peripheral blood samples, by calculating the number of circulating RBC, hemoglobin concentration (HB), packed cell volume (PCV), volumetric indices, such as mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC), a morphological examination at microscopic level (Messer, 1995;Kramer, 2000) and sometimes, examination of the bone marrow (Lording, 2008). When interpreting an equine hematological profile, some specific characteristics of this species should be kept in mind.…”
Section: Introduction and Specific Characteristics Of The Equine Erytmentioning
confidence: 99%
“…Similarly, assays of RBC creatine concentrations enable a more accurate evaluation of the erythropoietic response in horses. Mean RBC creatine concentration is significantly higher in young RBC populations (Wu et al, 1983), it shows a positive correlation with the reticulocyte count in bone marrow aspirates and a negative correlation with myeloid-erythroid ratio (Lording, 2008). However, it is not a common clinical procedure.…”
Section: Introduction and Specific Characteristics Of The Equine Erytmentioning
confidence: 99%